Developmental plasticity in reptiles: Critical evaluation of the evidence for genetic and maternal effects on temperature‐dependent sex determination. Issue 6 (25th June 2018) - Roush, Danielle; Rhen, Turk
Abstract: We critically review literature that examines variation in temperature‐dependent sex determination (TSD) within species. Although variation in sex ratio among clutches of eggs from different females is common in reptiles with TSD, the underlying mechanism that causes this variation is not clear. Authors have made claims about genetic variation in TSD and maternal effects on TSD. The latter type of study usually focuses on maternally derived steroids in egg yolk. Here, we outline the types of experiments and data required to unequivocally demonstrate that variation in sex ratio among clutches (1) has a genetic basis, (2) is caused by maternally derived steroids, or (3) is influenced by both factors. To date, few studies have met these requirements. GRAPHICAL ABSTRACT: There is substantial variation in temperature‐dependent sex determination among clutches of eggs produced by different females as well as among populations. Evidence to date suggests that genetic factors and maternally‐derived yolk steroids contribute to variation in thermosensitivity.